ANALISIS SEKTOR UNGGULAN DI KABUPATEN NAGAN RAYA TAHUN 2012 - 2017(Analysis of Leading Sectors in Nagan Raya Regency, in 2012 – 2017) - Safarul Aufa (JURNAL EKONOMIKA INDONESIA, 2019)
This study was aimed at highlighting the leading sectors of economy in Nagan Raya Regency. The data were gained from Gross Domestic Regional Product (GDRP) on the basis of diverse  economic sectors in Nagan Raya Regency from 2012 to 2017. This research utilized two types of calculation method, namely Location Quotient (LQ) and Klassen’s Typology method. When overlay was carried out between the method of LQ and Klassen’s Typology method, it could be concluded that sub-sectors of Agriculture, Animal Husbandry, Hunting  and Agricultural service were could classified as more leading sectors in Nagan Raya because these sectors suited the criteria of those two methods. Sub-sectors  of Forestry and Logging, and sectors of Mining and Excavation merely matched the criteria of LQ method.  Accordingly, construction sector was in line with Klassen’s Typology. However, the classifications of Klassen Typology method which encompassed the progressing and growing sector categories in Nagan Raya Regency were as follows 1) Sub-Sector of Agriculture, Animal Husbandry, Hunting and Agricultural Service and  2) Construction Sector. The potential sectors were  1) Industrial Processing Sector 2) Electricity Power Provision Sector 3) Accommodation, Drink and Food Sector 4) Finance and Insurance Service. However, the categories of saturated sectors included 1) Mining and Excavation and 2) and a Large Scale Business and a Retail Business, Car and Motorcycle Reparation. Meanwhile, the categories of lagging sectors were 1) Forestry  and Logging, 2) Sub-Sector of Fisheries 3) Water Provision, Garbage Management, Wastes and Recycling 4) Transportation and Warehousing; 5) Information and Communication; 6) Real Estate 7) Company Service 8) Government Administration; Defense and Required Social Security 9) Educational Service 10) Health Service; Social Activities and 11) Other sorts of services.